Does Cerebral Oxygenation Change during Peripherally Inserted Central Catheterization in Preterm Infants? - Ercan, Gözde; Imamoglu, Ebru Y.; Şahin, Özlem; Çolak, Derya; Imamoglu, Serhat (American Journal of Perinatology, 2023)
Objective This study aimed to evaluate the effect of peripherally inserted central venous catheterization on cerebral oxygenation by near-infrared spectroscopy in very low birth weight preterm infants.Study Design Forty-one preterm infants (gestational age ≤32 weeks and birth weight ≤1,500 g) requiring peripherally inserted central venous catheter were included. Hemodynamic data and cerebral regional oxygen saturation values measured by near-infrared spectroscopy were prospectively collected before (T0) and every 5 minutes for 30 minutes following catheterization. When compared with baseline (T0) values, those values having relative maximum changes in the first 15 minutes and between 15 and 30 minutes were defined as T15 max and T30 max, respectively. Any change of more than a 10% decrease in baseline cerebral rSO2 was considered clinically significant. Additionally, any changes exceeding 20% in heart rate and mean arterial blood pressure values were considered significant. Following catheterization, the time interval to reach the baseline for cerebral regional oxygen saturation was noted.Results Cerebral regional oxygen saturation values at T15 max and T30 max were found to have decreased significantly in 46 and 22% of patients, respectively. A statistically significant difference was observed between these two time periods (p = 0.002); no significant differences in heart rate, mean arterial blood pressure, or cerebral fractional oxygen extraction values at T15 max and T30 max were observed. All patients reached their baseline cerebral regional oxygen saturation in a median of 25 (15–60) minutes.Conclusion In very low birth weight preterm infants, monitoring cerebral regional oxygen saturation by near-infrared spectroscopy before and after peripherally inserted central venous catheterization may be useful in clinical practice. The assessment of factors affecting cerebral oxygenation and, in the case of low cerebral oxygenation, implementation of corrective actions before peripherally inserted central catheterization may offer a neuroprotective strategy.Key Points
Keywords: preterm; PICC line; NIRS; cerebral oxygenation